Understanding XBRL adoption process and adoption type among regulators: A Malaysian evidence - Ilias A.; Ghani E.K.; Azhar Z. (Primrose Hall Publishing Group, 2023)
Extensible Business Reporting Language (XBRL) has evolved over more than a decade and affects the financial reporting landscape worldwide. However, since its evolvement, XBRL has yet to be fully adopted around the world, particularly in Malaysia. This study aims at providing a better understanding on XBRL adoption by identifying the current state of XBRL adoption process and the type of adopters among the regulators in Malaysia. This study develops a framework by utilising the research framework developed by Rogers's (1983) adoption process. A case study approach consisting of interview with the regulators and thematic analysis were used. Based on the response of four regulators and documents analyses, this study found that the regulators are moving towards full XBRL adoption although slowly. Out of the four regulators, two regulators are considered early adopters whilst the remaining two regulators are an early majority. The findings of this study serve as a guideline for regulators and government agencies as well as contribute to the corpus of existing academic knowledge and literature. 2019, Primrose Hall Publishing Group.